2019
DOI: 10.3389/fncel.2019.00256
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic FUS Localization During Motoneuron Development and Its Accumulation in Human ALS Synapses

Abstract: Mutations in the fused in Sarcoma ( FUS ) gene induce cytoplasmic FUS aggregations, contributing to the neurodegenerative disease amyotrophic lateral sclerosis (ALS) in certain cases. While FUS is mainly a nuclear protein involved in transcriptional processes with limited cytoplasmic functions, it shows an additional somatodendritic localization in neurons. In this study we analyzed the localization of FUS in motoneuron synapses, these being the most affected neurons in ALS, using super-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 78 publications
2
31
0
Order By: Relevance
“…C to U mutations indicated with arrows and dashed circles, and 2-AP substitutions are denoted by solid circles. rodent synapses, and in human motoneurons derived from a healthy control induced pluripotent stem cells (Deshpande et al, 2019). Mouse studies suggest that synapses are significantly more susceptible to defects than axons and cell bodies when FUS is overexpressed or mutated (Sephton et al, 2016), indicating that FUS is important for synaptic plasticity and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…C to U mutations indicated with arrows and dashed circles, and 2-AP substitutions are denoted by solid circles. rodent synapses, and in human motoneurons derived from a healthy control induced pluripotent stem cells (Deshpande et al, 2019). Mouse studies suggest that synapses are significantly more susceptible to defects than axons and cell bodies when FUS is overexpressed or mutated (Sephton et al, 2016), indicating that FUS is important for synaptic plasticity and maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…However, a growing body of evidence has shown that FUS has an essential cytoplasmic role in neurons involved in transport and local protein translation, especially at the synapse. FUS has been shown to be located at both the pre- and post-synapse 8 , 9 as well as interacting with GluA1, the AMPA receptor subunit, which is a post-synaptic protein 10 . Evidence points towards FUS being essential for dendritic reorganisation by regulating synaptic mRNAs 11 , 12 with FUS depletion leading to a decrease in GluA1 expression resulting in supressed synaptic transmission and changes in synaptic maturation 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is a recent study in motor neurons derived from ALS patients in which an increased synaptic accumulation of mutated FUS is described, suggesting a role of synaptic FUS in both dendritic and axonal cellular compartments. In particular, a toxic gain‐of‐function due to the synaptic aggregation of mutant FUS was proposed (Deshpande et al, 2019).…”
Section: Introductionmentioning
confidence: 99%